The Aesthetic Reception of the Qur’an in Contemporary Music: A Case Study of Bersenja Gurau and Digital Audience Engagement Analysis - Muh. Awaluddin Awal; Rifki Ahmad Fahrezi; Andi Mujahidil Ilman SM; Muhammad Hasan (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2024)
According to William Graham, a text becomes sacred due to a relational connection between a faith community and the text they regard as holy. This relationship is manifested in various ways, such as accepting, reading, reciting, and treating the text with specific purposes. As a sacred text, the Qur’an is similarly received by faith communities, one of which is through musical expression. Recently, a song titled Bersenja Gurau (literally: Evening Jests) by Indonesian musician Raim Laode achieved widespread digital circulation. The artist claimed that the song contains quotations from the Qur’an, intended to expose listeners to the words of Allah. This study employs qualitative research methods using the Qur’anic reception framework developed by Ahmad Rafiq and Wolfgang Iser’s concept of aesthetic reception. To analyze the song’s impact on netizens, the study incorporates mass communication effect theory, including cognitive, affective, and behavioral effects. The findings reveal that Raim Laode’s activity of quoting the Qur’an in a song constitutes an aesthetic reception of the Qur’an. Moreover, based on netizen responses, Bersenja Gurau induces cognitive, affective, and behavioral effects. This research contributes to the development of the Living Qur’an studies by exploring the aesthetic reception of the Qur’an in popular music, offering a novel approach within academic discourse.